(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: Turnaround time (TAT) in a clinical biochemistry laboratory refers to the total time taken from when a test is ordered to when the result is reported back to the clinician. The study aims to evaluate the TAT time of the clinical biochemistry lab, assessing the pre-analytical and post-analytical phases’ relative contributions to the TAT in comparison to the analytical phase and determining the quantity of samples reported outside the specified TAT. A number of actions that could shorten the turnaround time overall were also assessed. Materials and methods: The study was conducted at GKGH Hospital, Kachchh, a district hospital, to evaluate the turnaround time (TAT) on samples analyzed in the clinical Biochemistry laboratory. In the present study, TAT was evaluated for parameters such as RFT (Renal Function Test), SGPT (Serum glutamate Pyruvate transaminase), Electrolytes, Troponin, and ABG (Arterial Blood Gas analyzer). The samples were collected from the OPD and IPD. The clinical Biochemistry is equipped with Vitros DTS 5600 and 7600, a dry test-based auto-analyzer. Results: In the present study, the mean and SD were observed in case of RFT TAT was 78 ±41, SGPT TAT was 103±54, Troponin TAT was 78±33, ABG test TAT was 15±12, Electrolytes TAT was 76 ± 42. Conclusion: In the present study, Evaluation of TAT of basic emergency parameters, which are common tests done in the laboratory. We noticed the major cause of delayed TAT time is pre-analytic steps. By improving the phlebotomy procedure, sample transport flow, and sample preparation steps, the TAT time can be improved significantly.